Review of biodiesel synthesis technologies, current trends, yield influencing factors and economical analysis of supercritical process. (1st August 2021) - Qadeer, Muhammad Umer; Ayoub, Muhammad; Komiyama, Masaharu; Khan Daulatzai, Muteeb Ullah; Mukhtar, Ahmad; Saqib, Sidra; Ullah, Sami; Qyyum, Muhammad Abdul; Asif, Saira; Bokhari, Awais
Abstract: The current use of world energy is gradually shifting to renewable energy due to climate change concerns and environmental contamination. Renewable biomass energy is one of the greener options to satisfy the ever rising demand for cleaner energy. Contemporary work and development centred on converting these bio-based resources into effective gaseous and liquid fuels compliant with current infrastructure for petro based chemical production. Due to its clean, renewable and environmentally friendly nature, biodiesel is a possible alternative to petroleum fuels. For the processing of cleaner biodiesel production, the transesterification cycle is used. There is extensive research in progress to establish more effective methods for biodiesel processing. The various new technologies recognise both solid catalysts and non-catalytic supercritical processes. This paper reviews the current status of biodiesel production, mainly under supercritical conditions. A review of different methods employed for biodiesel's effective synthesis includes the homogenous/heterogenous/enzymes catalysed synthesis, microwave/ultrasonic-assisted synthesis followed by more focusing on the supercritical synthesis of biodiesel. This critical review reports the current status of the supercritical process for biodiesel synthesis and the different parametric behaviour for the significant influence of process yield. The supercritical biodiesel production method is a simple way of achieving an energy saving of 71.6% and energy savings of just 17.8% as compared to the other biodiesel production processes. An economic analysis along with the conclusion and future perspective has been reported. Graphical abstract: Image 1 Highlights: Supercritical biodiesel synthesis offers 71.6% less energy consumption. Supercritical has 1.42 folds' higher production rate than conventional biodiesel process. Supercritical production cost is 1.06 folds lower than conventional biodiesel process. A biodiesel yield of >99% was achieved in a supercritical reactor.